Answer:
![f_1=(f_2)/(2)](https://img.qammunity.org/2020/formulas/physics/college/2uroouf5x851z0eyrkfndrcwxe9df19jcq.png)
Step-by-step explanation:
the Frequency of string is given by
![f= (1)/(2l)*\sqrt{(T)/(\mu )}](https://img.qammunity.org/2020/formulas/physics/college/ve5dnrs5gg5gb9hklx4gklyt4vj5px57ed.png)
T= tension in the string
μ= mass per unit length of string
l= length of string
in the given question
= 4
![\mu_(2)](https://img.qammunity.org/2020/formulas/physics/college/1rdtpyngubu5cn5fgw6wjvubhouu8s4jl1.png)
here subscript 1 is massive string and subscript 2 is lighter string
![f_(1)= (1)/(2l)*\sqrt{(T)/(\mu_(1) )}](https://img.qammunity.org/2020/formulas/physics/college/knh0wfyjgfbq9eh0krq6ihsr3f2vfi5j8l.png)
and
![f_(2)= (1)/(2l)*\sqrt{(T)/(\mu_(2) )}](https://img.qammunity.org/2020/formulas/physics/college/zr8uz53ff9wpmmboyf02b3hcfgtugyb88m.png)
dividing f_1 by f_2 we get
now
![(f_(1))/(f_(2)) =\sqrt{(\mu_2)/(\mu_1) }](https://img.qammunity.org/2020/formulas/physics/college/78iqqv5qzxnktcjokhevb3voltx6br8zlh.png)
=
![\sqrt{(\mu_2)/(4\mu_2) }](https://img.qammunity.org/2020/formulas/physics/college/5remkcwivuv3zrwqe8mcn6sn0av8f372id.png)
=
![(1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ybjkeso7qr5r7js5h0mv9de35dih0sxfpl.png)
⇒
![f_1=(f_2)/(2)](https://img.qammunity.org/2020/formulas/physics/college/2uroouf5x851z0eyrkfndrcwxe9df19jcq.png)
hence the fundamental frequency of massive string is half of the fundamental frequency of lighter string